PERMINTAAN DARAH PERSIAPAN TINDAKAN BEDAH DI RSUP DR. WAHIDIN SUDIROHUSODO - Herlinah Herlinah; Rachmawati Muhiddin; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Surgical procedures frequently need blood transfusion. However, the blood demand is frequently excessive without an appropriateneed analysis. The high percentage of canceled and returned blood indicates the ineffective use of blood transfusion. To know theappropriateness of blood demand for surgery preparation at the Dr. Wahidin Sudirohusodo General Hospital the researchers analyzedhis matter. This study was an observational study with cross sectional approach. The data of the blood demand for surgery preparationwere obtained from the blood bank of the Dr. Wahidin Sudirohusodo General Hospital, Makassar during August up to November 2013.The data were grouped based on the number of blood demand and the quantity of canceled and returned blood, these were then analyzedby SPSS software. The total of samples which were identified was about 1599 with 3829 blood demands. The quantity of canceled bloodwas1915 and the returned blood was 730. The demand of blood products indicated that whole blood was 2340 (61.3%), PRC 1392(36.4%), platelets 83 (2.2%) and FFP 5 (0.1%). The highest blood demand was observed in the General Surgery Department 797(20.9%). The difference between blood demand and the returned blood quantity (for whole blood and PRC) was analyzed statisticallyand indicated a significant result (p=0.000), this meant that there was a mismatch between blood demand number and the returnedblood quantity. This matter could reflect the ineffective use of blood transfusion.